Analysis of transition metal dichalcogenides materials based gas sensor using non‐equilibrium green's function. (29th May 2022) - Kumar, Prateek; Gupta, Maneesha; Singh, Kunwar; Kumar, Naveen
Abstract: Gas sensors play a crucial role in fields extending from environmental to medical sciences. Modern FET‐based gas sensors have their own set of problems, so, in this work, an ultra‐small and highly sensitive TMDC material‐based gas sensor is proposed. Investigated nanowire‐based gas sensor has a radius and length of 4 nm and 20 nm respectively. Catalytic materials Molybdenum and Palladium are used as gate electrodes. MoS2, MoTe2 and WS2 are used as channel materials for the detection of Ammonia and to sense Hydrogen, MoS2 is used. The work function of catalytic materials changes due to the physical adsorption/chemisorption of gases. To include the quantum effects and to enhance the accuracy of results, along with Schrodinger‐Poisson equations, non‐equilibrium Green's function is used as a principle simulation model. Variations in characteristics of the sensor are explained on basis of transmission probability, density of states at source and drain electrode. For the detection of Ammonia, WS2 resulted in the highest ION /IOFF sensitivity of 1523 and MoS2 can detect Hydrogen at ION /IOFF sensitivity of 1137. The device investigated can be used in the future for the detection of the aforementioned gases.